Climate Change: How it Affects the European Security - Markopoulou, Angeliki-Efraimia (HAPSc Policy Briefs Series, 2021)
This policy brief, in the context of environmental policy, addresses the issue of climate change and whether it affects the European security. The chronic and ever-increasing problem of climate change, in addition to its obvious consequences in the fields of agriculture, health, economy and others, can now create "gaps" in the security of states, in ways that will be explained. Some current issues related to the analysis will be announced, the European Union’s positions on the problem will be reported and in addition the positions of UN officials and especially the Security Council will be reported. Then some suggestions-recommendations will be given aimed at addressing the problem.